A characterization of uninorms on bounded lattices by means of triangular norms and triangular conorms. Issue 8 (17th November 2018) - Çaylı, Gül Deniz
ABSTRACT: Uninorms are generalizations of triangular norms and triangular conorms leaving the freedom for the neutral element to be an arbitrary element from a bounded lattice. In this paper, we study uninorms on bounded lattices and investigate their main characteristics. We also introduce the new construction methods for uninorms on bounded lattices with a neutral element based on the fact that the presence of triangular norms and triangular conorms. Furthermore, we assess and exemplify the differences between our constructions and the present approaches.